Lower leg arterial calcification assessed by high-resolution peripheral quantitative computed tomography is associated with bone microstructure abnormalities in women. Issue 11 (November 2016) - Paccou, J.; Edwards, M.; Patsch, J.; Jameson, K.; Ward, K.; Moss, C.; Dennison, E.; Cooper, C.
Abstract Summary In older women, the presence of lower leg arterial calcification assessed by high-resolution peripheral quantitative computed tomography is associated with relevant bone microstructure abnormalities at the distal tibia and distal radius. Introduction Here, we report the relationships of bone geometry, volumetric bone mineral density (BMD) and bone microarchitecture with lower leg arterial calcification (LLAC) as assessed by high-resolution peripheral quantitative computed tomography (HR-pQCT). Methods We utilized the Hertfordshire Cohort Study (HCS), where we were able to study associations between measures obtained from HR-pQCT of the distal radius and distal tibia in 341 participants with or without LLAC. Statistical analyses were performed separately for women and men. We used linear regression models to investigate the cross-sectional relationships between LLAC and bone parameters. Results The mean (SD) age of participants was 76.4 (2.6) and 76.1 (2.5) years in women and men, respectively. One hundred and eleven of 341 participants (32.6 %) had LLAC that were visible and quantifiable by HR-pQCT. The prevalence of LLAC was higher in men than in women (46.4 % (n = 83) vs. 17.3 % (n = 28), p < 0.001). After adjustment for confounding factors, we found that women with LLAC had substantially lower Ct.area (β = −0.33, p = 0.016), lower Tb.N (β = −0.54, p = 0.013) and higher Tb.Sp (β = 0.54, p = 0.012) at the distal tibia and lower Tb.Th (β = −0.49, p = 0.027) at the distal radius compared with participants without LLAC. Distal radial or tibial bone parameter analyses in men according to their LLAC status revealed no significant differences with the exception of Tb.N (β = 0.27, p = 0.035) at the distal tibia. Conclusion In the HCS, the presence of LLAC assessed by HR-pQCT was associated with relevant bone microstructure abnormalities in women. These findings need to be replicated and further research should study possible pathophysiological links between vascular calcification and osteoporosis.